THE CLUE IS IN THE THYROID FUNCTION TEST - Tong , Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Less than 50 cases of primary pituitary lymphoma (PPL) have been reported in the literature. We present a 52-yearold Malaysian male who was diagnosed with PPL after being investigated for four years. Our patient presented with alternating third and sixth nerve palsies. Initial CT of the brain was normal. His thyroid function tests then showed low free T4 of 6.9 pmol/l (11.5-22.7) and low TSH of 0.08 miu/l (0.55-4.78). Further anterior pituitary assessment showed low cortisol and central hypogonadism. A large homogenous infiltrative lesion in the sella, measuring 5.1 x 3.3 x 3.4 cm was found on pituitary MRI. He underwent debulking of the tumor. Histopathology examination revealed a diagnosis of non-Hodgkin’s lymphoma. He subsequently underwent chemotherapy followed by radical whole-brain radiotherapy. Low Free T4 and TSH in the setting of multiple cranial nerve palsies is an important clue to suspect a pituitary lesion.